Islamic Work Ethics in Building Work Life Balance to Achieve Islamic Job Satisfaction - Eviatiwi Kusumaningtyas Sugiyanto; Taufikur Rahman; Aprih Santoso (State Institute of Islamic Studies (IAIN) Salatiga, 2020)
The purpose of this study is to provide an interpretation of library studyresult on the relationship between Islamic Work Ethics (IWE) in buildingwork life balance (WLB) to achieve job satisfaction in Islam. The methodused is library study by tracing related topics. Data comes from primarysources in the form of articles that are relevant to topics. Meanwhile,data analysis used interpretive. The results show that there is an allegedlogical relationship between IWE, WLB and job satisfaction in Islam.Application of IWE can build a balance between work and life outsideof work. Furthermore, someone who is able to build this balance can feeljob satisfaction, in terms of Islamic job satisfaction. The implication ofthis research, there is an initial assumption of a link between IWE andWLB and job satisfaction in Islam. The future research agenda can testempirically the relationship between these variables by incorporating itinto an empirical research model.